Impulsive buying in Live Streaming Commerce: The Role of Flow Experience, Parasocial Interaction and Immersion Relationship - S Sipur; Amadi, Jaman (CV. Media Digital Publikasi Indonesia, 2025)
The paradigm shifts and changes in consumer behavior have evolved alongside technological advancements and the progress of time. Since the COVID-19 pandemic, the use of online media has become widespread, including buying and selling activities. The increasing interest in online shopping has led many shopping centers to go bankrupt, which also impacts local tax revenues. This study aims to analyze the influence of flow experience, parasocial interaction, and immersion on impulsive buying tendencies in e-commerce live streaming. Data were collected from 400 respondents who are active users of live streaming platforms such as Shopee, TikTok, and Instagram in Medan. The study was conducted in 2024. The research employed the Stimulus-Organism-Response (S-O-R) method and was analyzed using SEM (Structural Equation Modeling). The study consisted of two phases: the Pilot Test and the Main Test. Data were collected through the distribution of questionnaires. The results show that in the goodness of fit test, two indices met the criteria: CMIN/DF (3.576), CFI (0.915), and SRMR (0.07). However, one index, RMSEA (0.085), did not meet the criteria. The SEM analysis results indicate that the standardized coefficient β > 0 and the p-value ≤ 0.05, showing that the hypothesis is accepted. Thus, there is a relationship between flow experience (p < 0.05), parasocial interaction (p < 0.01), and immersion (p < 0.001) on impulsive buying tendencies. This study also shows that the stronger the consumers' flow experience and parasocial involvement, the more likely they are to make impulsive purchases during live streaming